Multiterritory Atherosclerosis and Carotid Intima‐Media Thickness as Cardiovascular Risk Predictors After Percutaneous Angioplasty of Symptomatic Subclavian Artery Stenosis. (27th July 2016) - Wrotniak, Leszek; Kablak-Ziembicka, Anna; Karch, Izabela; Pieniazek, Piotr; Rosławiecka, Agnieszka; Mleczko, Szymon; Tekieli, Lukasz; Zmudka, Krzysztof; Przewlocki, Tadeusz
Abstract : Objectives: To identify independent predictors of cardiovascular events among patients with subclavian artery stenosis. Methods: Two hundred eighteen consecutive patients with subclavian artery stenosis referred to angioplasty were examined for coexistent coronary, renal, or lower extremity artery stenosis of 50% or greater. Initial carotid intima‐media thickness and internal carotid artery (ICA) stenosis were assessed. Intima‐media thickness was reassessed in 108 randomly chosen patients to evaluate the change over time. The incidence of cardiovascular death, myocardial infarction (MI), ischemic stroke, and symptomatic lesion progression was recorded. Results: The patients included 116 men and 102 women (mean age ± SD, 62.1 ± 8.4 years). Isolated subclavian artery stenosis and involvement of 1, 2, and 3 or 4 other territories with stenosis of 50% or greater were found in 46 (21.1%), 83 (38.1%), 55 (25.2%), and 34 (15.6%) patients, respectively. Internal carotid artery stenosis of 50% or greater (relative risk [RR], 1.54; 95% confidence interval [CI], 1.39–1.70; P < .001) and initial intima‐media thickness (RR, 1.16; 95% CI, 1.05–1.28; P = .005) were identified as independent markers of multiterritory atherosclerosis. The optimal intima‐media thickness cutoff for atherosclerosis extent was 1.3 mm (sensitivity, 75.6%; specificity, 76.1%). During follow‐up of 57 ± 35 months, cardiovascular death, MI, and ischemic stroke occurred in 29 patients (13.3%). Those patients had significantly higher intima‐media thickness progression (+0.199 ± 0.57 versus +0.008 ± 0.26 mm; P = .039) and more widespread initial atherosclerosis (mean territories, 1.8 ± 1.1 versus 1.3 ± 1.1; P = .042). Independent predictors of cardiovascular death, MI, ischemic stroke, and lesion progression were coronary artery disease (RR, 1.32; 95% CI, 1.10–1.58; P = .003) and intima‐media thickness progression (RR, 1.22; 95% CI, 1.02–1.46; P = .033; sensitivity, 75.0%; specificity, 61.8%). Conclusions: In patients with symptomatic subclavian artery stenosis, baseline carotid intima‐media thickness and ICA stenosis of 50% or greater are associated with multiterritory atherosclerosis, whereas intima‐media thickness progression is associated with the risk of cardiovascular events.